2010
DOI: 10.1093/hmg/ddq103
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking defects and loss of ligand binding are the underlying causes of all reported DDR2 missense mutations found in SMED-SL patients

Abstract: Spondylo-meta-epiphyseal dysplasia (SMED) with short limbs and abnormal calcifications (SMED-SL) is a rare, autosomal recessive human growth disorder, characterized by disproportionate short stature, short limbs, short broad fingers, abnormal metaphyses and epiphyses, platyspondyly and premature calcifications. Recently, three missense mutations and one splice-site mutation in the DDR2 gene were identified as causative genetic defects for SMED-SL, but the underlying cellular and biochemical mechanisms were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 34 publications
3
75
0
Order By: Relevance
“…The Algerian family had a different mutation: c.2177T>G [1726R] [100] . In 2010, Ali et al [101] reported on the same mutation in a family from Egypt as originally reported by alGazali et al in 1996 [99] and on a novel mutation in a family from Pakistan who had a milder phenotype.…”
Section: Spondylometaepiphyseal Dysplasia Short-limb-abnormal-calcifmentioning
confidence: 56%
“…The Algerian family had a different mutation: c.2177T>G [1726R] [100] . In 2010, Ali et al [101] reported on the same mutation in a family from Egypt as originally reported by alGazali et al in 1996 [99] and on a novel mutation in a family from Pakistan who had a milder phenotype.…”
Section: Spondylometaepiphyseal Dysplasia Short-limb-abnormal-calcifmentioning
confidence: 56%
“…Mutations may alter kinase activity, ligand binding, or DDR2 localization (28,29). In a study by Hammerman and colleagues (30), mutations were found in 11 of 290 SCC samples (3.8%).…”
Section: Membrane Receptor Alterationsmentioning
confidence: 99%
“…Loss of function of human or mouse Ddr2 gene leads to dysplasia in bones [20,21,22,23]. Therefore, the regulation of DDR2 in osteoblast differentiation is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Ddr2 knockout mice and slie mice (mouse colony with spontaneous autosomal-recessive mutation in the Ddr2 locus) exhibit short long bones and irregular growth of flat bones [20]. Human Ddr2 gene mutation causes a rare form of dwarfism, spondylo-meta-epiphyseal dysplasia short limb-hand type (SMED-SL) [21,22,23]. Our and other's studies also demonstrated that DDR2 plays essential roles in osteoblast differentiation and chondrocyte maturation by modulating the phosphorylation and transactivity of Runx2 in an ERK MAPK-dependent manner [24,25].…”
Section: Introductionmentioning
confidence: 99%